2018
DOI: 10.18388/abp.2017_2305
|View full text |Cite
|
Sign up to set email alerts
|

Lower levels of Caveolin-1 and higher levels of endothelial nitric oxide synthase are observed in abdominal aortic aneurysm patients treated with simvastatin

Abstract: This study was undertaken to verify whether simvastatin modulates Cav-1/eNOS expression, and if this modulation is associated with changes in pro- and anti-inflammatory cytokine and Toll-like receptor 4 (TLR4) level in abdominal aortic aneurysm (AAA). It is a 1:2 case-control study of non-statin (n=12) and simvastatin-treated patients (n=24) who underwent open AAA repair. Simvastatin treatment decreased Cav-1 (p<0.05) and increased eNOS expression (p<0.01) in the AAA wall. These changes might be dose dependent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 39 publications
(43 reference statements)
0
8
0
Order By: Relevance
“… 10 Furthermore, simvastatin treatment decreased Cav1 expression and increased eNOS (endothelial nitric oxide synthase) expression in patients who underwent abdominal aortic aneurysm repair. 11 The study highlighted a potential link between statins and Cav1 and additionally suggested a possible pleiotropic benefit of statins outside of lipid reduction. Statins may exert their effects on eNOS through Cav1 as endocytosis of caveolae has been shown to mediate the activation of eNOS.…”
mentioning
confidence: 92%
“… 10 Furthermore, simvastatin treatment decreased Cav1 expression and increased eNOS (endothelial nitric oxide synthase) expression in patients who underwent abdominal aortic aneurysm repair. 11 The study highlighted a potential link between statins and Cav1 and additionally suggested a possible pleiotropic benefit of statins outside of lipid reduction. Statins may exert their effects on eNOS through Cav1 as endocytosis of caveolae has been shown to mediate the activation of eNOS.…”
mentioning
confidence: 92%
“…In addition to their lipid-lowering capacity, statin can improve endothelial function via increasing endothelial nitric oxide synthase expression and BH4 bioavailability (Kosmidou et al, 2007;Wenzel et al, 2008). In contrast, statin treatment can also diminish IL-6 and MCP1 levels in AAA models (Kowalska et al, 2018). In this study, we focused on the protective effects of endothelium-specific BRG1 deletion in AAA, and our results demonstrated that BRG1 deletion in endothelial cells significantly inhibited Ang II-induced AAA development.…”
Section: Discussionmentioning
confidence: 87%
“…The core function of the endothelium is to provide an anti-adhesive, antithrombotic surface. Cytokines and hypercholesterolaemia stimulate endothelial dysfunction and result in impaired production of endothelial nitric oxide synthase (eNOS) (30)(31)(32). NO mediates several benefits, including vascular relaxation and suppression of smooth-muscle-cell proliferation, leukocyte, or platelet-endothelial interactions and exocytosis (33).…”
Section: Anti-inflammatory Actions Of Statinsmentioning
confidence: 99%